Role of Guidance and Counseling In the Personality Development of Secondary School Students: Addressing Complex Challenges in Secondary School Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
We are social beings and, so in some way or other we needhelp and guidance of others. Mother, father, grandparents, and teachers and otherelders as well as home, school and society guide youngsters for successfulliving. The student’s life is getting complex day by day. Students in  the twenty-first century have  facing many complex and difficult situationsi.e. to make wise curricular and  othercurricular choices, to acquire basic study skills for  optimum achievement, adjustment with peersetc. Due  to explosion  of knowledge, industrialization and  changes in socio-economic setup the need of professional guidance is  felt  in   the  present day society. In   the  present time the  aim  of education  is  to achieve the fullest  possible  realization of possibilities inherent inthe  individual. The education fostersall aspects of an individual‘s personality.